PENGARUH PENDIDIKAN DAN PENDAPATAN ISTRI TERHADAP KESEJAHTERAAN EKONOMI KELUARGA DI KECAMATAN CIOMAS - Sukarnaesih , Heni; Waki, Ahmad; Misno (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
Ciomas District is one of the sub-districts in Bogor Regency, one of the sub-districts located close to Bogor City. Ciomas District consists of 10 villages and 1 sub-district, which has 150 posyandu and 789 posyandu cadres who always dedicate themselves to social activities, especially in the health sector. The livelihoods of residents of Ciomas District are private employees, civil servants, factory workers as a source of family economy. Ciomas District has succeeded in maintaining population growth. However, the number of unemployed increases, especially during the pandemic from 2020 to 2022, this results in family economic difficulties, which in the end, wives participate in helping the family economically. The formulation of the problem in this research is how the wife's education level and income influence the family's economic welfare. The method used is quantitative with test equipment using classical assumption tests and multiple linear regression analysis. Overall, the results of multiple linear regression analysis and hypothesis testing can be concluded that partially (T test) the wife's education level and income have a significant effect on the family's economic welfare. Simultaneously (F test) shows that the variables of the wife's education level and income have a simultaneous influence on the family's economic welfare with a significance <0.05 With the education that wives have, they can help the family economically. With formal, informal or non-formal education, wives hope to get a better job with sufficient wages for the family. Likewise with income, wives hope that with a high income the family's economic welfare will be guaranteed